Performance and Pest and Disease Resistance Tests Local Genotype of Lowland Rice - Oktaviandra Putra; ediwirman edi wirman; Salfiati Salfiati (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2023)
Rice is a food commodity with economic value as the main staple to maintain national and global food stability. The need for rice is in genotype with population growth, so it is necessary to increase production and productivity. The development of superior varieties requires genetic resources from local rice genotypes from West Sumatra regions, including Marapulai, Silih Baganti, Bujang Marantau, Hitam Manih, Junjuang, Mundam, Papanai and so on. Information on plant performance tests related to growth, agronomic components, and resistance to pests and diseases of local genotypes of lowland rice is still very limited. The experiment aimed to obtain local genotypes of lowland rice that had the appearance and resistance to pests and diseases. The observed growth and yield components were planting height, number of productive tillers, flowering age, ripening age, panicle length, number of seeds per panicle, number of good seeds per panicle, 1000 grain weight, and dry grain weight per ha. Pest and disease resistance variables are; brown planthopper pests, bacterial leaf blight and blast disease. Observational data were analyzed by F test at 5% level with the Least Significant Difference (LSD) at 5%. Analysis using PC software program Statistix ver 8.0. Collected data are observing pest and disease resistance based on assessment standards from the International Rice Research Institute. Based on the growth and agronomic components of the experiment, Maraplai was one of the genotypes that could be used as a superior variety, with the resistance of brown planthopper biotypes 1, 2 and 3 to making them susceptible. Marapulai local genotype has better growth and yield characteristics, as well as resistance to pests and diseases.